Targeting orthotopic and metastatic pancreatic cancer with allogeneic stem cell–engineered mesothelin-redirected CAR-NKT cells - Yan-Ruide Li; Xinyuan Shen; Enbo Zhu; Zhe Li; Jie Huang; Thuc Le; Catrina Tran; Caius G. Radu; Lili Yang (Proceedings of the National Academy of Sciences, 2025)
Pancreatic cancer (PC) remains one of the leading causes of cancer-related mortality worldwide. The majority of patients are diagnosed at advanced stages, with over 50% presenting with metastatic disease at the time of diagnosis. Although chimeric antigen receptor (CAR)-T cell therapy has shown promise in targeting PC, its clinical efficacy remains limited due to several critical challenges. These include tumor antigen heterogeneity, antigen loss or escape mechanisms, functional exhaustion of CAR-T cells within the tumor microenvironment, as well as inherent limitations of autologous approaches such as high manufacturing costs, prolonged production timelines, and restricted scalability. To address these challenges, we developed allogeneic IL-15–enhanced, mesothelin-specific CAR-engineered invariant natural killer T ( Allo15 MCAR-NKT) cells through gene engineering of human hematopoietic stem and progenitor cells (HSPCs) using a clinically guided culture method. These Allo15 MCAR-NKT cells exhibited robust and multifaceted antitumor activity against PC, driven by both CAR and NK receptor–mediated cytotoxic mechanisms. In orthotopic and metastatic human PC xenograft models, Allo15 MCAR-NKT cells demonstrated superior tumor control, enhanced trafficking and infiltration into tumor sites, sustained effector and cytotoxic phenotypes, and reduced expression of exhaustion markers. Importantly, Allo15 MCAR-NKT cells demonstrated a favorable safety profile, characterized by the absence of graft-versus-host disease and minimal cytokine release syndrome. Collectively, these findings validate Allo15 MCAR-NKT cells as a promising next-generation, off-the-shelf immunotherapeutic approach for PC, with the potential to overcome critical challenges including tumor heterogeneity, immune evasion, and therapeutic resistance, especially in the context of metastatic disease.